1995
DOI: 10.1038/378496a0
|View full text |Cite
|
Sign up to set email alerts
|

Topographical representations of mental images in primary visual cortex

Abstract: We report here the use of positron emission tomography (PET) to reveal that the primary visual cortex is activated when subjects close their eyes and visualize objects. The size of the image is systematically related to the location of maximal activity, which is as expected because the earliest visual areas are spatially organized. These results were only evident, however, when imagery conditions were compared to a non-imagery baseline in which the same auditory cues were presented (and hence the stimuli were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
281
5
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(326 citation statements)
references
References 16 publications
37
281
5
3
Order By: Relevance
“…Consistent with the findings of Ring et al (1999), subjects with autism in the present study demonstrated greater activity in right occipital cortex, which is involved in the visual processing of objects (Kosslyn et al 1995), extending into the inferior temporal region (Ring et al 1999). The occipital, inferior temporal, and inferior parietal activity observed is also consistent with the activation patterns in adults with AD (Baron-Cohen et al 1994) and implicates spatial visual processing pathways (Ungerleider et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of Ring et al (1999), subjects with autism in the present study demonstrated greater activity in right occipital cortex, which is involved in the visual processing of objects (Kosslyn et al 1995), extending into the inferior temporal region (Ring et al 1999). The occipital, inferior temporal, and inferior parietal activity observed is also consistent with the activation patterns in adults with AD (Baron-Cohen et al 1994) and implicates spatial visual processing pathways (Ungerleider et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…", Goel and Dolan, 2001;Knauff et al, 2003;Prado et al, 2010b). To illustrate the impact of these distinctions on brain activations, relational problems may recruit posterior parietal regions (e.g., Goel and Dolan, 2001;Knauff et al, 2003) that are known to underlie the kind of spatial representation evoked by transitive relations like "taller than" (Kosslyn et al, 1995;Prado et al, 2010b). Such regions would not be expected for connectives, which seem devoid of spatial interpretation.…”
Section: Deductive Domainsmentioning
confidence: 99%
“…When a subject is asked to ''imagine'' a particular image the frontal lobes invariably come on line. Feedback connections from the frontal lobes to the posterior lobes are thought to activate the same circuits that would be activated if the actual image had been presented to the retinas (Kosslyn et al, 1995). Furthermore, the eye movements of subjects asked to imagine a particular scene reflect the content and spatial arrangement of objects populating the scene (Mast and Kosslyn, 2002).…”
Section: Other Frontal Lobe Functionsmentioning
confidence: 99%